Applying Data Mining on Personal Computer for Document Classification - Chai, Ian; Salleh, Ahmad Zarif (Society of Visual Informatics, 2025)
The typical user creates documents over many years of computer usage. As people move from computer to computer, they tend to copy the files to the new computer, because